COMPETENCE TASKS AS A MEANS OF BUILDING INFORMATICS COMPETENCE UNDER CONTINUOUS EDUCATION (Journal of Information Technologies in Education (ITE), 2010)
This article discusses the implementation of the competency approach in the context of the transition to continuing education. Highlighted the general approach of competence in order to create tasks of IT competence - invariant in the system of key competences in the information society and improve the quality of education in general. There are examples of use tasks for computer competence in the various stages in the system of continuous education.
Keywords: competence tasks; computer competence; the principle of continuous education